Basic Course (B-Course) for Disaster Health Management (DHM) Development and Its Challenges for the Application to Each ASEAN Member States (AMS) - Phummarin Saelim; Phumin Silapunt; Dangfun Promkhum (Universitas Gadjah Mada, 2025)
Introduction: Capacities on health-related competencies of the disaster response team among ASEAN Member States (AMS) are diverse with different strengths and weaknesses. In order to maximize the optimal outcome of joint disaster response operations, a training program that provide common fundamental concepts on disaster health management is essential. The Basic Disaster Health Management training course (BDHM) is one of the proposals under the plan for the Project for strengthening the ASEAN Regional Capacity on Disaster Health Management (ARCH project) to provide a solution to this problem. Objective: To describe the development process of the BDHM course as well as the challenges for the application and ways forward. Methods: The main author reviewed all the reports of the Sub-Working Group meeting on curriculum development and related articles as well as described the observed outcome of the training activities of the BDHM course. Result: BDHM course is one of the outstanding results of the ARCH project. It aims to provide basic knowledge on disaster medicine, skills, and attitudes for the health-related disaster response team. The course was developed to include a module on constructing learners' competencies, content generation, and the planning of learning methodology. All processes have been conducted by the committee of the Sub-working Group on Curriculum Development and approved by the Project Working Group. Experts from the AMS and Japan have contributed to the development of this course. The course had already been implemented including the initiative course that had been conducted in Surat Thani, Thailand, and the mock-up course in Bangkok. The results of the very first implementations were fruitful, but there was still a lot of room for improvement. Discussion and conclusion: Further implementation in other member states is necessary to achieve the goal of the plan of action of the ARCH project and it is expected that the course will provide the standard guideline for the disaster response team in the AMS in the future.